Walking Many Paths, Our Research Journey to (Re)present Multiple Knowings: Creating our own spaces - Hogarth, Melitta; Czuy, Kori (Engaged Scholar Journal, 2021)
Indigenous peoples globally are seeking new ways in which to communicate and share our worldviews.  Sometimes defined as resistance research, emancipatory research, decolonising research - our research (re)presents the multiple journeys in which we live and come to know. Emerging Indigenous research methodological approaches are centring Indigenous ways of knowing, being and doing, to privilege Indigenous voices that have been suppressed through colonization.  The intricate weaving of Western methodologies with Indigenous knowledges evokes agency in two emerging Indigenous researchers (from Australia and Canada) and weaves a path of reconciliation between their diverse disciplines as well as the seemingly dichotomous knowledge systems they are challenged to work within. Using metalogue, a way of authentically bringing together multiple voices through dialogue, we discuss the creative and radical Indigenous methodological approaches developed and enacted within our PhDs.  The paper will provide insights to the epistemological, ontological and axiological principles that inform emerging Indigenous approaches to research.